TINJAUAN YURIDIS KUMULASI GUGATAN ANTARA PERBUATAN MELAWAN HUKUM DAN WANPRESTASI (STUDI PUTUSAN MA NOMOR. 2157 K/PDT/2012 DAN PUTUSAN MA NOMOR. 1330 K/PDT/2017) - Fauzan Azima Faturachman; Maudy Anjani; Kinayah Ashifa; Esa Rahmawati; Farahdinny Siswajanthy (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the cumulation of lawsuits that are justified according to procedural rules in Indonesia based on general principles from the analysis of two Supreme Court decisions, because in essence there are no rules in Indonesian civil procedural law that prohibit the cumulation of lawsuits but there are decisions that do not allow the cumulation of lawsuits between tort and default. The absence of rigid rules prohibiting the cumulation of claims in Indonesian civil procedure law a contrario allows the cumulation of claims. However, in practice, there is a Supreme Court decision whose rulings contradict each other, namely decision number. 2157 K/Pdt/2012 which grants the cumulation of lawsuits and decision number. 1330 K/Pdt/2017 which states that the lawsuit cannot be accepted. Based on the analysis of the two Supreme Court decisions, the general principle of the formulation of lawsuit cumulation that is justified by the Indonesian procedural rules can be drawn, namely that there is a close relationship, legal relationship and compatibility between the statement and the petitum.